Apakah Anggaran Pemasaran Pariwisata Pemerintah Efektif dalam Meningkatkan Jumlah Kunjungan Wisatawan? - Sukirman, Oman (THE Journal : Tourism and Hospitality Essentials Journal, 2017)
Our focus is the effect of the tourism ministry budget to promote tourism on the growing number of tourists. We used regression models using data for 2011 through 2016 to identify the impact of tourism marketing budgets on the growth in tourist numbers. The results show that the effect of higher marketing on the growth of the number of tourists depends on the level of tourism marketing budget that is in the ministry of tourism. More specifically, the results show that tourism marketing budgets have a major effect in increasing the number of foreign tourists visiting. However, the effect is different if applied to national tourism marketing. For the national tourism marketing budget is less effect in increasing the number of domestic tourists.